Exploring English Speaking Anxiety in EFL Context: A Lesson from First Year University Students - Khalilullah, Mochammad Nur Faqih; Ekowijayanto, Mochlis (JOLLT Journal of Languages and Language Teaching, 2026)
English-speaking anxiety remains a significant challenge for EFL learners, particularly in higher education contexts where students are expected to communicate actively in English despite limited linguistic competence and classroom exposure. In socio-religious learning environments such as Islamic higher education institutions, speaking anxiety may also be influenced by cultural and communicative norms. Therefore, this study aimed to investigate the level, perceptions, and contributing factors of English-speaking anxiety among first-year EFL students at Nurul Jadid University.This study employed a mixed-methods design involving 43 first-year students aged 18–20 years enrolled in a second-semester speaking course. Quantitative data were collected using the English-Speaking Anxiety Scale (ESAS), while qualitative data were obtained through semi-structured interviews. The data were analyzed using descriptive statistics and content analysis.The findings revealed that vocabulary limitation was the primary factor contributing to students’ speaking anxiety, followed by low self-confidence, fear of making mistakes, and limited opportunities for speaking practice. Pedagogical factors, including classroom atmosphere and teacher support, also influenced students’ anxiety levels. In addition, the socio-religious learning environment shaped students’ communication behavior and classroom participation.The study suggests that supportive and context-sensitive pedagogical approaches are essential to reduce speaking anxiety and improve students’ communicative competence in EFL classrooms. This research contributes to the understanding of speaking anxiety within Islamic higher education contexts and highlights the importance of integrating linguistic, psychological, pedagogical, and socio-cultural considerations in EFL instruction.